Assessment of the nervous system state in low birth weight children taking into account the FADS2 rs174583 (C/T) gene polymorphism - Shumna, T. Ye.; Levchuk-Vorontsova, T. O.; Шумна, Таміла Євгенівна; Левчук-Воронцова, Тетяна Олегівна; Шумная, Т. Е.; Левчук-Воронцова, Т. О. (Запорізький державний медичний університет, 2020)
Aim. To assess the neurological status and index of neuropsychological development in low birth weight children taking into account the FADS2 rs174583 (C/T) gene polymorphism. Materials and methods. To study the FADS2 rs174583 (C/T) gene polymorphism, 170 children were examined. The children were divided into 3 groups depending on their birth weight: group I included 53 children (birth weight was 1500–1999 g, gestation period – 33.0 [32.0; 35.0] weeks), group II included 77 children (birth weight – 2000–2499 g, gestation period – 35.0 [34.0; 36.0] weeks), group III was composed of 40 children as a control (birth weight – more than 2500 g, gestation period – 38.0 [36.0; 39.0] weeks). The genotyping was carried out using a polymerase chain reaction method. Results. The C allele and the С/Т genotype frequencies of the FADS2 rs174583 gene polymorphism in the children matched those in North-Western Europe. Seizures in the past medical history due to the nervous system disorders were most commonly occurred in children with the TT genotype (16.45 %, P < 0.05), while patients with the CC genotype had seizures in only 5.6 % of cases. Children with a birth weight of 1500–1999 g carrying the C/T heterozygous genotype and the T/T homozygous genotype of the FADS2 (rs1745683) gene polymorphism had a lower total Apgar score than children with a birth weight of more than 2000 g (P < 0.05). The coefficient of psychomotor development was the lowest in children with birth weight of 1500-1999 g and the minor homozygous T/T genotype of the FADS2 (rs1745683) gene polymorphism, at 83.0 (75.0; 83.0), which corresponded to a weak normal level of the neuropsychiatric development, while the highest index of psychomotor development (116.0 (112.0; 141.0)) and a normal high level of neuropsychiatric development were significantly registered in children with birth weight of 2500 g and the major homozygous C/C genotype. Conclusions. It is possible that the predominance of the homozygous C/C genotype and the heterozygous C/T genotype fulfils a protective function in order to reduce the negative effects of preterm birth on the nervous system. Мета роботи – оцінити неврологічний стан та індекс нервово-психічного розвитку дітей, які народжені з низькою масою тіла, враховуючи поліморфізм С/Т гена FADS2 (rs1745683). Матеріали та методи. Для вивчення поліморфізму С/Т гена FADS2 (rs174583) обстежили 170 дітей, яких поділили на 3 групи залежно від ваги під час народження: І група – 53 дитини із вагою під час народження 1500–1999 г, строком гестації – 33,0 [32,0;35,0] тижня; ІІ група – 77 дітей із вагою під час народження 2000–2499 г, строком гестації 35,0 [34,0; 36,0] тижня; ІІІ група (контролю) – 40 дітей із вагою під час народження понад 2500 г, строком гестації – 38,0 [36,0; 39,0] тижня. Генотипування здійснили методом полімеразної ланцюгової реакції. Результати. Частота виявлення алеля С поліморфізмом С/Т гена FADS2 (rs174583) відповідає показникам південно-західної Європи. Ураження нервової системи, як-от судоми, частіше реєстрували в дітей із генотипом ТТ (16,45 %, р < 0,05), а в пацієнтів із генотипом СС судоми визначали в 5,6 % випадків. Діти з масою тіла під час народження 1500–1999 г (гетерозиготи та гомозиготи за алелем ТТ) мали вірогідно меншу суму балів за шкалою Апгар, ніж діти з вагою понад 2000 г (p < 0,05). Найнижчий коефіцієнт психомоторного розвитку визначили в дітей із масою тіла під час народження 1500–1999 г і мінорним гомозиготним генотипом ТТ поліморфізму С/Т гена FADS2 – 83,0 (75,0; 83,0); найвищий показник психомоторного розвитку (116,0 (112,0; 141,0)) частіше реєстрували в дітей із масою тіла під час народження понад 2500 г і генотипом СС. Висновки. Імовірно, переважання домінантного генотипу СС і гетерозиготного генотипу СТ відіграє протекторну функцію для зменшення негативного впливу з боку нервової системи, що пов’язаний із передчасним народженням. Цель работы – оценить неврологическое состояние и индекс нервно-психического развития детей, родившихся с низкой массой тела, учитывая полиморфизм С/Т гена FADS2 (RS174583). Материалы и методы. Для изучения полиморфизма С/Т гена FADS2 (rs174583) обследовали 170 детей. Детей поделили на 3 группы в зависимости от веса при рождении: I группа – 53 ребенка с весом при рождении 1500–1999 г, сроком гестации 33,0 [32,0; 35,0] недели; II группа – 77 детей с весом при рождении 2000–2499 г, сроком гестации 35,0 [34,0; 36,0] недели; III группа (контроля) – 40 детей с весом при рождении больше 2500 г и сроком гестации 38,0 [36,0; 39,0] недели. Генотипирование провели методом полимеразной цепной реакции. Результаты. Частота обнаружения аллеля С полиморфизма С/Т гена FADS2 (rs174583) приближалась к показателям северо-западной Европы. Поражение нервной системы в виде судорог чаще всего регистрировали у детей с генотипом ТТ (16,45 %, р < 0,05), а у пациентов с генотипом СС судороги отмечены только в 5,6 % случаев. Дети с весом при рождении 1500–1999 г (и гетерозиготы, и гомозиготы по аллелю Т) имели достоверно более низкую оценку по шкале Апгар, чем дети с весом более 2000 г (p < 0,05). Индекс психомоторного развития самый низкий у детей с массой тела при рождении 1500–1999 г с минорным гомозиготным генотипом гена FADS2 (rs1745683), составляя 83,0 (75,0; 83,0); самый высокий показатель индекса психомоторного развития (116,0 (112,0; 141,0)) достоверно чаще регистрировали у детей с генотипом СС и массой тела при рождении более 2500 г. Выводы. Вероятно, преобладание доминантного генотипа СС и гетерозиготного генотипа СТ имеет протекторную функцию для защиты нервной системы от негативного влияния, связанного с преждевременным рождением.
Оцінювання стану нервової системи дітей, які народжені з низькою масою тіла, враховуючи поліморфізм С/Т гена FADS2 (rs174583)
Оценка состояния нервной системы детей с низкой массой тела при рождении, учитывая полиморфизм С/Т гена FADS2 (RS174583)
Keywords: alleles; genotypes; polyunsaturated fatty acids; preterm birth; children; алельні гени; генотипи; поліненасичені жирні кислоти; передчасні пологи; діти; аллельные гены; генотипы; полиненасыщенные жирные кислоты; преждевременные роды; дети